(untitled) (Third Sector Social Economic Review, 2017)
In today’s world of increased competition along with technological developments and globalization, public entities and institutions and the private sector are in search of alternatives for providing optimal service with decreased costs. In addition to technological advances, human capital is a major source for institutions to tap into in order to boost their efficiency. Therefore, the human resource management (HRM) plays a crucial role in the private and public sector management in the new world order with harsher competition rules. The human resources which organizations need to survive and become successful can be obtained from motivated, high-performing employees. The new public management system wields these methods to provide more effective, efficient and rational services. Since 1980s, there have been efforts to reinforce the local administrations which are administrative units that are the closest to the public and which complement the central government in the areas where the latter fails to provide the full range of public services. Although they were originally raised for central governments, the concepts and issues of performance, quality, effectiveness, efficiency, strategic planning, etc., have come to be discussed and implemented for local administrations as well. Due to their place and position within the existing administrative structure and as a result of their lack of infrastructure required for performance management, local administrations largely fail to achieve the goals set for them.